Bamboo Construction: Main Building Techniques and Their Resources, Sustainability, History, Uses, and Classification - De Araujo, Victor Almeida; Colauto, Letícia Rubio [UNESP]; Abel, Leticia Gabriele Crespilho [UNESP]; do Rosário, Fábio Silva [UNESP]; Vasconcelos, Juliano Souza [UNESP]; Morales, Elen Aparecida Martines [UNESP]; Barbosa, Juliana Cortez [UNESP]; Gava, Maristela [UNESP]; Christoforo, André Luis (Springer Nature, 2023)
Like wood, bamboo is utilized in different products for civil construction, either in natural or in engineered form. The easy proliferation in small-sized planted forests, rapid harvest cycles, and low environmental impacts in the planting and processing stages gave significant credentials to this renewable bio-based resource in the last years. In addition, different bamboo species are likely to be applied to structural applications. These facts value this biomaterial as a convenient input to supply the civil construction sector, above all, in more sustainable housing and infrastructure. Formerly, bamboo culms and esterillas were used in popular buildings using rudimentary solutions based on vernacular techniques. From the advancement of bioresource technology and industrialization, structural bamboo products and bamboo-based composites are being developed for modern buildings manufactured from prefabrication techniques. As a structural material in its multiple forms, bamboo can be used alone or together with other materials, which contributes to the diffusion of this commodity worldwide. Thereat, bamboo buildings may overcome their usual applications in Asia, Africa, and part of Latin America to be valued as a sustainable alternative for construction by engineering and architecture professionals from Europe, Oceania, and South and North Americas.
Keywords: Bamboo; Bamboo construction; Bio-construction; Bioproducts; Construction technique; Green architecture; Sustainable bioresources; Sustainable housing